Water scarcity in coastal Bangladesh: Search for arsenic-safe aquifer with geostatistics - Hassan, M. Manzurul; Shaha, Anamika; Ahamed, Raihan (Springer Link, 2024)
This book chapter was published in the book named Climate, Environment and Disaster in Developing Countries and the definite version is available at : https://link.springer.com/chapter/10.1007/978-981-16-6966-8_6